Problematika Sarana dan Prasarana dalam Proses Belajar Mengajar di SD Negeri 104202 Bandar Setia - Khairunnisa Khairunnisa; Irda Yani Dongoran; Khadijah Gani Harahap; Nabila Assyifa Lubis; Yola Adelya Azhar; Ade Haerunisa (Journal on Education, 2024)
Currently, Indonesian education faces several challenges in its efforts to achieve global competitiveness in various fields. Various efforts have been made to improve education standards, including expanding educational opportunities in various fields, such as through improving facilities and infrastructure. Education management, simply called learning management, is a tool to help students achieve learning goals. Several methods are used in education management, including organizing, planning, directing, and forming relationships in the field of education. In this publication, we mainly discuss the state of infrastructure quality that is still lacking in order to facilitate the learning process in schools. The literature study method is the technique used in this qualitative research project. In order to collect information for this research, comprehensive observations and interviews were carried out at SD Negeri 104202 Bandar Setia. The data collected resulted in a gap in the quality of primary and secondary school equipment.